Augmented Reality-Based Application Design for the Introduction of Rattan Furniture - Elma Tryana; Lili Rusdiana (Journal of Applied Science and Technology, 2022)
Design is one of the important stages in building applications, also in building applications based on augmented reality. Augmented reality can visualize images into 3D forms for rattan furniture objects. This study aims to design applications in the introduction of furniture, so that the introduction of interior furniture is carried out through applications without having to go to furniture sales locations. There are 5 pieces of furniture that are included in the design of augmented reality-based applications, namely tables, chairs, sofas, cabinets, and baskets. Interface design using balsamiq wireframes. The design is also carried out by describing the design description through storyboards. Designing the use of augmented reality through image content on cards that function as markers. The data collection method used to design the application is the method of observation and literature.